2005
DOI: 10.1142/s0217732305017652
|View full text |Cite
|
Sign up to set email alerts
|

REPRESENTATION OF THE HEISENBERG ALGEBRA h4 BY THE LOWEST LANDAU LEVELS AND THEIR COHERENT STATES

Abstract: Using simultaneous shape invariance with respect to two different parameters, we introduce a pair of appropriate operators which realize shape invariance symmetry for the monomials on a half-axis. It leads to the derivation of rotational symmetry and dynamical symmetry group H4 with infinite-fold degeneracy for the lowest Landau levels. This allows us to represent the Heisenberg–Lie algebra h4 not only by the lowest Landau levels, but also by their corresponding standard coherent states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…n and m. On the other hand, the 2D and 3D models representing the algebraic relations (12) for p = 2k are some known quantum mechanical models on the homogeneous manifolds SL(2, c)/GL(1, c) and the group manifolds SL(2, c). Now in order to obtain the mentioned representations, we only introduce two bunches of the shape invariance models which have been classified before [11,25]. In master function theory, a function A(x) which is at most of second order in terms of x, and a non-negative weight function W (x) defined in an interval (a, b) may be chosen so that (1/W (x))(d/dx)(A(x)W (x)) is a polynomial of at most first order.…”
Section: Towards An Appropriate Generalization Of the B-d Parasupersymentioning
confidence: 99%
See 3 more Smart Citations
“…n and m. On the other hand, the 2D and 3D models representing the algebraic relations (12) for p = 2k are some known quantum mechanical models on the homogeneous manifolds SL(2, c)/GL(1, c) and the group manifolds SL(2, c). Now in order to obtain the mentioned representations, we only introduce two bunches of the shape invariance models which have been classified before [11,25]. In master function theory, a function A(x) which is at most of second order in terms of x, and a non-negative weight function W (x) defined in an interval (a, b) may be chosen so that (1/W (x))(d/dx)(A(x)W (x)) is a polynomial of at most first order.…”
Section: Towards An Appropriate Generalization Of the B-d Parasupersymentioning
confidence: 99%
“…In master function theory, a function A(x) which is at most of second order in terms of x, and a non-negative weight function W (x) defined in an interval (a, b) may be chosen so that (1/W (x))(d/dx)(A(x)W (x)) is a polynomial of at most first order. For a given master function A(x) and its corresponding weight function W (x), it has been shown that the eigenvalue equations of the one dimensional partner Hamiltonians corresponding to the first bunch of the superpotentials, which are obtained from the factorization with respect to the main quantum number n, will be [25]…”
Section: Towards An Appropriate Generalization Of the B-d Parasupersymentioning
confidence: 99%
See 2 more Smart Citations